DIAGNOSIS OF EMOTIONAL AND VOLITIONAL SELF-REGULATION OF PRIMARY SCHOOL AGED PUPILS' IN TERMS OF THE VOCAL AND CHORAL ACTIVITIES - Olga A. Malakhova (Russian State Vocational Pedagogical University, 2015)
The aim of the study is to investigate emotional and volitional self-regulation of primary school children during musical activities such as a choral performance.Methods. The proposed method of diagnosing emotional and volitional selfregulation in the process of choral activities, and methods of mathematical statistics are applied. Results and scientific novelty. The author formulates the definition of emotional and volitional self-regulation; criteria and indicators for its diagnosis are developed. The main criteria for the development of emotional and volitional selfregulation are: «self-control in the process of hearing musical performance», «emotional performance of a musical work», and «arbitrary regulation of psychophysiological state». The data obtained in the course of diagnosis in the Ural College of Music in vocal and choral activities at primary school children are analyzed. The use of mathematical statistics to summarize the data is justified.Practical significance. The development techniques of emotional and volitional self-regulation of future musicians to choral exercises are described; this technology may be used in music colleges, children's art schools, as well as the highest level of musical performing and musical-pedagogical education. Research materials can be useful both to psychologists, and experts in the field of music education.